Standardising Responsibility? The Significance of Interstitial Spaces - Wickson, Fern; Forsberg, Ellen-Marie (Science and engineering ethics, 2015)
Modern society is characterised by rapid technological development that is often socially controversial and plagued by extensive scientific uncertainty concerning its socio-ecological impacts. Within this context, the concept of ‘responsible research and innovation’ (RRI) is currently rising to prominence in international discourse concerning science and technology governance. As this emerging concept of RRI begins to be enacted through instruments, approaches, and initiatives, it is valuable to explore what it is coming to mean for and in practice. In this paper we draw attention to a realm that is often backgrounded in the current discussions of RRI but which has a highly significant impact on scientific research, innovation and policy—namely, the interstitial space of international standardization. Drawing on the case of nanoscale sciences and technologies to make our argument, we present examples of how international standards are already entangled in the development of RRI and yet, how the process of international standardization itself largely fails to embody the norms proposed as characterizing RRI. We suggest that although current models for RRI provide a promising attempt to make research and innovation more responsive to societal needs, ethical values and environmental challenges, such approaches will need to encompass and address a greater diversity of innovation system agents and spaces if they are to prove successful in their aims.